Fidelity of implementation of healthcare provider-oriented care and support to people with leprosy for disability prevention and management in Rupandehi district, Nepal - Nepal, Sudip; Probandari, Ari; Timilsina, Amit; Joshi, Prakash Chandra; Ahmad, Riris Andono (BKM Public Health and Community Medicine, 2024)
Purpose: Leprosy, or Hansen’s disease, is a chronic infectious disease likely transmitted by prolonged, close contact with untreated leprosy patients through nasal and oral droplets. Left untreated can lead to irreversible nerve, skin, face, hand, and foot impairments. Healthcare providers should assess and monitor the disease's progress and treat complications. This study aimed to explore the fidelity of implementation of healthcare provider-oriented care and support to people with leprosy for disability prevention and management in the Rupandehi district of Nepal. Methods: This implementation study used a qualitative approach and a multi-source, multi-method case study design to accomplish study objectives. Purposive and selective sampling techniques were used in this study. Focused Group Discussion (FGD), Key Informant Interview (KII) and Observation checklist were used for data collection. Thematic analysis was carried out for the data analysis. Results: The study highlights that healthcare providers adhere to protocols for accurate diagnosis and comprehensive treatment, while challenges include the lack of skin smear test facilities. Patient satisfaction is influenced by timely services, counseling, and access to assistive devices. Various barriers to leprosy services such as financial hardships during referrals, high transportation costs, inconsistent drug supply, inadequate infrastructure, and lack of trained personnel, hinder effective treatment. However, facilitators such as adequate staffing, family involvement, effective communication, external partner support, trained staff, and transportation incentives enhance leprosy services. Conclusion: The study identified major barriers to leprosy services and facilitators enhancing the leprosy services. Addressing these barriers while leveraging facilitators is crucial to the care and support of people with leprosy for disability prevention and management.